Spontaneous T Cell Proliferation: A Physiologic Process to Create and Maintain Homeostatic Balance and Diversity of the Immune System - Min, Booki (Frontiers in Immunology, 2018)
Naive T lymphocytes undergo heterogeneous proliferative responses when introduced into lymphopenic hosts, referred to as “homeostatic proliferation” and “spontaneous proliferation”. In particular, spontaneous proliferation is a unique process through which the immune system generates memory phenotype cells with increasing TCR repertoire complexity. Here, the mechanisms that initiate and control spontaneous proliferation are discussed.